IMPLANT-PROSTHETIC REHABILITATION OF UNIDENTARE EDENTATION - PRINCIPLES OF TREATMENT - Nicolae Vasile; Viorel Ibric (Romanian Society of Oral Rehabilitation, 2015)
For a practitioner with experience, the restoration with one or two individual crowns is relatively simple from clinical and technical point of view, but if a single crown has to be rebuilt in areas with major aesthetic concern, the prosthetic restoration becomes a challenge for any team of professionals. A major challenge for such a team si the unidental restoration, with or without implants, of a single incisor from the frontal maxillar area, especially the central superior incisors. These teeth have a highly aesthetic part since they are in direct connection with the shape and the aspect of the face. In the evaluation of the dental shape of the central incisors we can use different parameters which are closely related to the individual anatomical aspects of each patient: the shape and aspect of the face, the analysis of the existing casts or photos from the youth of the patient with the natural teeth. Finally, the decision is taken together with the patient after we establish the expectations and his possible personal demanding. By comparison with the frontal area, the restoration of the posterior teeth presents some advantages: •The width of the initial alveolar crest is greater in the posterior area next to the frontal one; •The vestibular wall is denser and more extensive and allows the 4-5mm implant placement; • The esthetic aspect of the cervical area of the posterior teeth including the interdental spaces and the gingival papilae are less demanding than the frontal esthetical regions; •The esthetics of the shape of the crowns, the emerging profile of the crowns as well as the colour shades are less pretentious; •The placement of an implant in a unidental lateral space spares the practitioner of the preparation of the neighbouring teeth to the edentulous space, resulting a few advantages. We should not forget that, through the increasingly modern methods of mass media spreading, the patient is more curious and informed, consequently more demanding. All these requirements must be weight and if achievable, they will be analysed by the medical team then discussed with the patient.